Realization of the Vilnius photometric system for CCD-observations of selected sky areas at the Andrushivka Astronomical Observatory - Andruk, V.; Butenko, G.; Gerashchenko, O.; Ivashchenko, Yu.; Kovalchuk, G.; Lokot', V.; Samoylov, V. (Кинематика и физика небесных тел, 2005)
We describe a set of glass UPXYZVS filters of the Vilnius photometric system of the Andrushivka Astronomical Observatory in Zhytomyr Region (Ukraine) [7]. They are installed at the Zeiss-600 Cassegrain reflector together with the 15-bit 1024×1024 CCD-camera S1C-017. The response curves of instrumental photometric systems are presented and a comparison of them with a standard system are analysed. Test observations in the Vilnius system of the star cluster IC 4665 with the Andrushivka filters were carried out in May–June 2003. The MIDAS/ROMAFOT and ASTROIMAGE software is adapted for digital processing of CCD-images of stellar fields. Comprehensive ground-based observations are being planned to design a catalogue of primary UPXYZVS CCD-standards in selected areas of the sky where are with radio sources, globular and open clusters, etc.